Occupational leg edema—use of compression stockings. Issue 6 (24th November 2020) - Guedes, Pedro M.; Saldanha, Nuno A.; Matos, Pedro M.; Carvalho, Francisco S.; Veiga, Graça; Norton, Pedro
Abstract : Abstract: To analyze the use of compression stockings to avoid the formation of occupational edema of the lower limbs in jobs with prolonged orthostatism. We carried out a review of the articles published in PubMed, from the 1st of January 2008 to 31st of December 2018 using the term "Occupational Leg Swelling". Only articles that met the following criteria were selected: prospective, observational and experimental retrospectives articles written in Portuguese or English. The research resulted in 23 articles. After reading the titles and abstracts and applying the inclusion and exclusion criteria, 5 were selected. Prolonged orthostatism is considered a risk factor for the development of chronic venous disease. The use of compression stockings reduces the occupational edema of the lower limbs. Professionals exposed to prolonged orthostatism during their work activity have a higher risk of developing lower limb edema; Despite few studies demonstrated the effectiveness of wearing compression stockings to prevent occupational edema of the lower limbs, they have showed benefit in reducing edema as well as associated symptoms. The use of compression stockings should therefore be recommended to all professionals at increased risk for occupational edema of the lower limbs.